2016
DOI: 10.2350/15-08-1682-cr.1
|View full text |Cite
|
Sign up to set email alerts
|

Fetus with Casamassima-Morton-Nance Syndrome and Limb–Body Wall Defect: Presentation of a Novel Association and Review of the Phenotype

Abstract: In 1981, Casamassima and colleagues described an autosomal recessive syndrome of spondylocostal dysostosis associated with anal and urogenital anomalies. Here, I describe 1 new fetus who presented with limb-body wall defect as a novel association, compile 7 patients, and review the clinical phenotype of Casamassima-Morton-Nance syndrome. This appears to be the 1st Casamassima-Morton-Nance syndrome fetus with this complex malformation. In light of this manifestation, a detailed comparative phenotypic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…1 However, Thauvin-Robinet et al 2 reported associated features of left fibula agenesis. Salinas-Torres 3 also said a case of CMNS with limb-body wall defect. The present case had bilateral clubfoot in association with the other common findings of CMNS and partial agenesis of the sacrum, which was earlier documented only in the case reported by Salinas-Torres.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 However, Thauvin-Robinet et al 2 reported associated features of left fibula agenesis. Salinas-Torres 3 also said a case of CMNS with limb-body wall defect. The present case had bilateral clubfoot in association with the other common findings of CMNS and partial agenesis of the sacrum, which was earlier documented only in the case reported by Salinas-Torres.…”
Section: Discussionmentioning
confidence: 98%
“…2 4 Other differential diagnoses include cerebro-facio-thoracic dysplasia (OMIM 213980) but lack of a neurological involvement, which seems to be a constant feature in all reported cases, excluding diagnosis. 3…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis is the ultimate causative factor for restrictive lung disease as it will be progressively worsened with growth. This can be achieved by addressing the thoracic insufficiency by performing multiple expansion thoracoplasties with vertical expandable prosthetic titanium rib VEPTR instrumentation (Synthes) [ 9 , 10 ]. Ramirez et al reported 20 patients with SCD who had VEPTR device with a 2-year follow-up and showed promising results [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic disruption as well as poor timing of vascular transition involves essential processes such as angiogenesis, apoptosis, and cell migration. From our perspective, this biological scenario might be demonstrative for those cases displaying a constellation of co-occurring anomalies [3,64,65], or perhaps fetal demise, particularly when associated with maternal toxic exposures, given that more than one disruptive event may occur, even after the embryonic period [66]. Of note, cell deposition may also be massively reduced between the abdominal wall and the amnion, which could lead to an extensive defect of the abdominal wall along with detrimental consequences to the abdominal organs and cord [49].…”
Section: Discussionmentioning
confidence: 99%